GENERAL POINTS ABOUT THE INFECTION BY HAEMOPHILUS PARASUIS IN SWINE – REVIEW (Revista de Ciências Agroveterinárias, 2005)
The Haemophilus parasuis is a Gram-negative, nonhemolytic, nonmotile and nicotinamide adenine dinucleotide (NAD) dependent bacterium, commonly found in the nasal cavity of healthy swine. However, it is also the cause of Glässer’s disease, characterized by polyserositis, polyarthritis and meningitis in young pigs. This review highlights general aspects about the infection, including etiology, epidemiology, pathogenesis, clinical signs, lesions, diagnosis, prevention and control of the disesase.
Keywords: Haemophilus parasuis; polyserositis; swine.